Serum sphingomyelin levels define oxyhemoglobin desaturation-related metabolic threshold in symptomatic obstructive sleep apnea - Ott Kiens; Egon Taalberg; Viktoria Ivanova; Ketlin Veeväli; Triin Laurits; Ragne Tamm; Aigar Ottas; Kalle Kilk; Ursel Soomets; Alan Altraja (Scientific Reports)
Abstract Hypoxia is a contributing factor for the morbidity and mortality in patients with obstructive sleep apnea (OSA). We aimed at identifying the percentage of sleep time with oxyhemoglobin desaturation below 90% (Tc90%) breakpoint from which the most significant changes occur in systemic metabolome of patients with OSA. In a prospective observational study on patients with polysomnography–confirmed symptomatic OSA, profiles of 186 metabolites including amino acids, biogenic amines, acylcarnitines (AC), lysophosphatidylcholines, phosphatidylcholines (PC) and sphingomyelins (SM) were analyzed with liquid chromatography-mass-spectrometry in peripheral blood, obtained at 3 time points that covered patients’ night sleep. Comparisons of rank-transformed data with general linear model for repeated measures after dichotomizing the study group at different Tc90% levels were applied to define the best cut-off, hypoxic metabolic threshold (HMT), based on Cohen’s f. Fifty-one subjects were recruited with their median Tc90% of 2.1. The mean Cohen’s f over the metabolites was highest (0.165) at a Tc90% of 1.8 representing the HMT. Of the different classes of metabolites, the Cohen’s f value at HMT was highest for SM (0.322). Compared to patients with Tc90% < HMT, concentrations of 2 PC, 1 AC and 7 SM were significantly higher in patients with Tc90% ≥HMT. The HMT for patients with OSA described in this report for the first time is located at a Tc90% level of 1.8 with SM levels contributing most to the size of this threshold.